Metal coordination study at Ag and Cd sites in Crown Thioether complexes through DFT calculations and hyperfine parameters - Nascimento, Rafael R. do (2015)
Structural and electronic properties of [C12H24S6X], [C13H26S6OX], and [C14H28S6OX] (X: Ag+ , Cd2+) crown thioether complexes were investigated within the framework of the density functional theory (DFT) using the projector augmented wave (PAW) method. The theoretical results were compared with time-differential perturbed γ?γ angular correlations (TDPAC) experiments reported in the literature using the 111Ag→111Cd probe. In the case of X=Ag+ , a refinement of the structure was performed and the predicted equilibrium structures compared with available X-ray diffraction experimental data. Structural distortions induced by replacing Ag+ with Cd2+ were investigated as well as the electric-field gradient (EFG) tensor at the Cd2+ sites. Our results suggest that the EFG at Cd2+ sites corresponds to the Ag+ coordination sphere structure, i.e., before the structural relaxations of the molecule with X=Cd2+ are completed. The results are discussed in terms of the characteristics of the TDPAC 111Ag→111Cd probe and the time window of the measurement, and provide an interesting tool with which to probe molecular relaxations.